Experimental and theoretical study of polyhedral carbon Nano-Onions - Basantes Valverde, Marlon Danilo; Pantano, Pietro; Caputi, Lorenzo; De Luca, Giorgio (My University, 2018)
Carbon nano-onions (CNOs), in their spherical or polyhedral forms, represent an important class of nanomaterials due to their peculiar physical and electrochemical properties. Among the different methods of production, arc discharge between graphite electrodes sustained by deionized water is one of the most promising to obtain good quality CNOs. The arc discharge method is applied to optimize the production of CNOs, and the synthesized nanomaterials by TEM was studied. An innovative experimental arrangement is used to obtain CNOs dispersed in water together with other carbon nanomaterials, and a black hard cathodic deposit. A simple mechanical grinding of the deposit it allowed to obtain turbostratic polyhedral CNOs with different aspect ratios, which exhibited higher stability towards burning in air, compared to CNOs found in water. A mechanism for the formation of the CNOs contained in the deposit, different from the generally accepted mechanism responsible for the synthesis of CNOs dispersed in water, is hypothesized. These spherical or polyhedral multi-shell fullerenes are widely studied owing to their interesting electronic and mechanical proprieties; nevertheless, comparative studies on these nanoparticles remain scarce. Herein, some key electronic proprieties of single and double walled icosahedral fullerenes as function of their sizes were calculated in the frame of the Density Functional Theory. In particular, structures of icosahedral polyhedral fullerenes, previously validated, were used to get the gap between the Highest Occupied Molecular Orbital and the Lowest Unoccupied Molecular Orbital levels (H-L gap), electron affinity, first ionization potential, electronegativity as well as the Density of the electronic States. This work shows that the H-L gap of the single-wall fullerenes decreases as the nanoparticles size increases, whereas an opposite trend was obtained for the double walled fullerenes. Going from single to double wall nanoparticles; a systematic and marked decrease of the H-L gap was found although, this difference reduces increasing the size of the double walled up obtaining an inversion. The DOS structures of SW nanoparticles changes radically adding a second shell, and the extent of these changes depends on the sizes of the analyzed fullerenes
Keywords: Carbon; Polyhedral